The transcendence of violence across relationships: new methods for understanding men's and women's experiences of intimate partner violence across the life course - Carbone-López, Kristin Carmela (Journal of quantitative criminology, 2012)
The notion of transitions is an increasingly central concept in contemporary criminology and such issues are particularly significant in the study of intimate partner violence (IPV). Here, attention focuses on relationship dynamics and movement into and out of relationships for understanding long-term patterns of victimization over the life course. Still, a focus on transitions raises questions about how IPV is patterned over time and across relationships and how this contributes to stability and change in victimization risk over the life span. Our study examines this issue using data from the National Violence Against Women Survey. Findings from latent transition analyses reveal strong evidence for change in victimization experiences across the life course. Among women, those who experienced serious, multifaceted violence are most likely to transition out of relationships followed by transition into subsequent relationships characterized by conflict and aggression and a similar pattern is observed among men. At the same time, men who experience physical aggression in previous relationships are most likely to transition into non-violent relationships, while women with similar experiences are much less differentiated in the types of relationships they enter into. When we account for background characteristics (e.g., respondent’s race, education, and age) and childhood experiences of parental violence, the latter is particularly significant in accounting for exposure to serious IPV in later adulthood. Such findings extend our understanding of how life course transitions connect to violence and offending and highlight processes of continuity and change beyond the traditional focus on criminal offending.